"Actua" project: secondary prevention in patients at high-cardiovascular risk. (14th October 2021) - Prieto Lobato, A; Corbi Pascual, M J; Redondo Prieto, M; Cubells Pastor, M; Muros Ortega, A; Carrasco Carrasco, E; Cordoba Soriano, J G; Martinez Pastor, A; Division Garrote, J A
Abstract: Introduction: It is acknowledged that secondary prevention for patients at high cardiovascular risk is suboptimal. Data from EUROASPIRE V registry showed that less than 50% of cardiovascular risks factors were controlled in this population. Purpose: "Actua" study was designed to identify potential gaps regarding secondary prevention for patients at very-high cardiovascular risk. The main objective was to assess differences between scientific evidence and clinical practice through an agreement/disagreement analysis of a questionnaire with statements based on clinical guidelines and expert recommendations. Methods: A qualitative analysis based on Delphi methodology was conducted. The study was divided into 2 phases. In phase 1, doctors were asked to show agreement or disagreement with the statements presented by the scientific committee through a Likert 5-points-scale. Consensus was stablished according to consensus method of Tastle. Results were expressed as a percentage (%CNS) which shows power of agreement or disagreement consensus. CNS>70% were considered as consensus. In phase 2, same doctors were asked again about the statements with no consensus or high dispersion in previous phase, after disclosing results in phase 1. In addition, a third questionnaire was conducted to asses socio-demographic data of the sample. Results: 246 and 265 questionnaires were conducted in phase 1 and 2 respectively. 90% of respondents in phase 1 and 94, 3% in phase 2 answered all the questions. Statements which showed consensus among participants are represented in table 1. As reported, there was consensus in goals for blood pressure (<130/80mmHg), cLDL (<70mg/dl), chronic use of acetylsalicylic acid in secondary prevention for coronary artery disease, stroke and peripheral artery disease. Doctors also agreed with the fact that 40mg atorvastatin can achieve 50% cLDL reduction levels from baseline. Scarce resources in secondary prevention were reported as main reason for medical attendants not following the best standards of care. Besides, most respondents agreed with the statement that a simpler treatment regime could improve therapeutical adherence in most patients. In phase 2, consensus was achieved in the statements showed in table 2. Conclusion: Doctors admitted that complex recommendations and lack of following-up were the main causes of low adherence to treatment among patients at high cardiovascular risk. Limitations: The study was conducted following recommendations from 2016 ESC/EAS guidelines for the management of dyslipaemias. FUNDunding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Grupo Ferrer Internacional, S.A.